Long-term rainfall trends and change points in hot and cold arid regions of India. Issue 7 (19th May 2017) - Machiwal, Deepesh; Dayal, Devi; Kumar, Sanjay
ABSTRACT: This study examined trends and change points in 100-year annual and seasonal rainfall over hot and cold arid regions of India. Using k -means clustering, 32 stations were classified into two clusters: the coefficient of variation for annual and seasonal rainfall was relatively high for Cluster-II compared to Cluster-I. Short-term and long-term persistence was more dominant in Cluster-II (entirely arid) and Cluster-I (partly arid), respectively. Trend tests revealed prominent increasing trends in annual and wet season rainfall of Cluster-II. Dry season rainfall increased by 1.09 mm year −1 in the cold arid region. The significant change points in annual and wet season rainfall mostly occurred in the period 1941–1955 (hot and cold), and in the dry season in the period 1973–1975 (hot arid) and in 1949 (cold arid). The findings are useful for managing a surplus or deficiency of rainwater in the Indian arid region.EDITOR A. Castellarin; ASSOCIATE EDITOR S. Kanae